Research on the prospects for obtaining iodine from carbohydrate fields in Ukraine - Mykhailovska, Olena (Academic journal Industrial Machine Building Civil Engineering, 2024)
The article describes that industrial waters are limited to deep parts of heavy hydraulic structures, mainly in zones of slow and very slow water exchange. It has been established that the production of iodine from reservoir waters is profitable under the condition that its concentration in the water is 18 mg/l. It is described that the concentration of iodine in formation waters of the Poltava region is 15-115 mg/l. Based on the results of water sample analysis, it was determined that the waters of the Andriyashiv gas condensate field have an iodine content of 15 mg/l or more. Water with an abnormally high iodine content of up to 115 mg/l was found among the samples of the Chizhivka field, the Rudivka gas field, the Lyman, and the Reshetnyaky oil and gas fields. It was determined that the specific gravity of the waters of the gas fields is usually low - from 1.071 to 1.085 g/cm3, and the water of the Reshetnyaky field is high - from 1.132 to 1.167 g/cm3. Formation waters of the following deposits were studied: Mashivka; Chutove; Raspashnivka; Novoukrainske; Lanna; Western Khrestyshche; Chervonoyarske; Western Starovirivske; Vedmedivka; Efremivka; Western Efremivske; Western Sosnivka; Kegichivka; Shebelinka from the intervals from 2520 to 5560 m. It was found that the mineralization of formation water was from 33.0 to 337.01 g/kg, the iodine content from 13.5 to 54.74 mg/l. It can be argued that the formation of groundwater with a high iodine content was significantly influenced by the considerable thickness of the sedimentary strata and the corresponding thermobaric conditions.
Keywords: reservoir water; iodine; deposit; raw materials